2016
DOI: 10.1097/wno.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus Surgery in Patients With Ocular Neuromyotonia: Potential Unmasking of the Condition and Effective Management Tool

Abstract: Background Ocular neuromyotonia is a rare motility disorder in which paroxysms of tonic extraocular muscle contraction from abnormal ocular motor nerve firing result in episodic diplopia and strabismus. Medical therapy with membrane-stabilizing agents has varied success. A surgical approach to treatment has not yet been described. We report the outcomes of strabismus surgery in patients with ocular neuromyotonia. Methods We describe three patients with sixth nerve paresis and ocular neuromyotonia of the affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition, it is worth noting that the patient's symptoms manifested after strabismus surgery, a phenomenon that has been reported before by Kim et al . 4 In their case series, 2 patients had medial rectus recession and lateral rectus resection before the onset of CN VI ONM. One theory to explain this observation is that ONM is initially masked preoperatively because of restriction by the antagonist muscle that prevents ocular rotation.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…In addition, it is worth noting that the patient's symptoms manifested after strabismus surgery, a phenomenon that has been reported before by Kim et al . 4 In their case series, 2 patients had medial rectus recession and lateral rectus resection before the onset of CN VI ONM. One theory to explain this observation is that ONM is initially masked preoperatively because of restriction by the antagonist muscle that prevents ocular rotation.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Surgical management can be an option after medical therapy. Strabismus surgery has been described for correction of ocular misalignment in ONM yet some cases of ONM occur after strabismus surgery for prior ocular disease [2 ▪▪ ,56]. Kim et al reported two patients with ONM after initial strabismus surgery and one patient with ONM following radiotherapy that underwent strabismus surgery for ocular misalignment, with subsequent resolution of their ONM [56].…”
Section: Treatmentmentioning
confidence: 99%
“…Strabismus surgery has been described for correction of ocular misalignment in ONM yet some cases of ONM occur after strabismus surgery for prior ocular disease [2 ▪▪ ,56]. Kim et al reported two patients with ONM after initial strabismus surgery and one patient with ONM following radiotherapy that underwent strabismus surgery for ocular misalignment, with subsequent resolution of their ONM [56]. Reviewing seven cases of resolved ONM following recession of the neuromyotonic muscle, they hypothesize that reducing the resting tension by weakening the neuromyotonic muscle may help mitigate spasms [56].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation